(untitled) (Journal of responsible AI & ethics, 2026)
Artificial Intelligence (AI) has become an integral part of modern businesses, particularly in consumer behavior prediction. The use of AI to predict consumer preferences, purchasing habits, and decision-making processes has revolutionized marketing strategies and customer relationship management. However, the widespread use of AI in predicting and influencing consumer behavior raises significant ethical concerns. These include issues related to privacy, bias, manipulation, and transparency in AI systems. This paper explores the ethical implications of AI in consumer behavior prediction, examining how AI systems are designed to influence consumer decisions and the potential consequences of these interventions. It delves into the ethical challenges of collecting and analyzing vast amounts of consumer data, the risks of algorithmic bias, and the potential for consumer exploitation through targeted advertising and personalized recommendations. The paper also discusses the importance of developing ethical frameworks for AI systems, ensuring that these technologies are transparent, accountable, and designed with fairness in mind. Through a combination of case studies, empirical research, and theoretical analysis, this paper provides insights into how businesses can mitigate the ethical risks of AI-driven consumer behavior prediction while maintaining trust and accountability in their use of AI.